THE EFFECTS OF OWNERS' PARTICIPATION AND LOCKUP ON IPO UNDERPRICING IN MALAYSIA - Wan Nordin Wan Hussin, (Asian Academy of Management Journal, 2005)
Recent theories of initial public offering (IPO) underpricing depart from the traditional asymmetric information models. Two recent IPO underpricing models are Habib and Ljungqvist (2001) and Brav and Gompers (2003). The Malaysian IPO market, characterised by high incidence of secondary offerings and IPO lockup commitments, provides a fertile ground to test the newer theories of IPO underpricing. Examining IPOs between August 1996 and June 2000 in Bursa Malaysia, the evidence lends support to the theoretical predictions that IPO underpricing is negatively related to owners' participation ratio and positively associated with the fraction of directors' shares which is subject to liquidity restrictions.